2016
DOI: 10.12989/sss.2016.17.6.859
|View full text |Cite
|
Sign up to set email alerts
|

Damage detection of a cable-stayed bridge based on the variation of stay cable forces eliminating environmental temperature effects

Abstract: Based on a recent work by the authors to separate the daily and long-term components of the effective temperature variation and cable force variation, this study first determines two transfer coefficients for these two components of effective temperature variation to eliminate the environmental temperature effects from the cable force variation. Several thresholds corresponding to different levels of exceedance probability are then obtained to establish four upper criteria and four lower criteria for damage de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…The corresponding coefficients are −0.96 and −0.85, respectively, in the summer. All these values are almost the same compared to those with EEMD (Chen et al., ).…”
Section: Rapidly Convergent Emdsupporting
confidence: 61%
See 1 more Smart Citation
“…The corresponding coefficients are −0.96 and −0.85, respectively, in the summer. All these values are almost the same compared to those with EEMD (Chen et al., ).…”
Section: Rapidly Convergent Emdsupporting
confidence: 61%
“…It was discovered that the cable force and effective temperature can both be categorized into two main components including the daily variation and the long‐term variation. The correlation analysis for the decomposed variations of both quantities also revealed that the correlation coefficient of their daily variations are no less than −0.97 in magnitude and that associated with their long‐term variation are mostly higher than −0.8 for various cases (Chen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Cho et al performed a comparative study of three different cable tension measurement methods of the EM sensor, the vibration‐based, and the traditional lift‐off test at the cable‐stayed Hwa‐Myung Bridge, located in Korea. Chen et al presented damage detection of cable‐stayed bridges based on variation of cable tension forces; the damage detection method was developed to eliminate the temperature effect on the relationship between the cable forces and the actual damage. An et al proposed a model‐free, output‐only, and fast damage diagnosis method for stay cables based on frequency change; frequency differences due to small damage of the stay cable are always submerged by the error of the parameter identification and surrounding noise; a temporary diagonal steel bar is installed with one end on the stay cable and the other end on the bridge deck, and then the stay cable is divided into a short part and a long part; as a result, the frequency changes due to small damage increases dramatically than that without the temporary diagonal steel bar; the method has been validated by simulation and experiment.…”
Section: Recent Progress On Damage Identification Methods For Cable‐smentioning
confidence: 99%
“…For this method, the fundamental natural frequency of stay cable can be used to determine the cable force. What should be emphasized is that the natural frequency is also affected by environment factors besides cable damage, and some study results have revealed that temperature is the most dominant environmental factor for cable‐stayed bridges, so the temperature‐induced effect on natural frequency should also be taken into account . Second, the acoustic emission method (AEM for short) .…”
Section: Introductionmentioning
confidence: 99%
“…Many cable parameters such as bending stiffness, boundary conditions, effective cable length, and sag extensibility should be taken into account for calculation of cable tension force, and for some cable parameters such as bending stiffness and sag extensibility, it is difficult to accurately weigh their influences for large‐diameter stay cables, especially when the stay cable has intermediate supports or dampers . Besides, although the cable damage can be detected by identifying the abnormal variation of time‐varying cable force or natural frequency, a further assessment on the damage degree of broken stay cables in the real environment is still one challenge for VM …”
Section: Introductionmentioning
confidence: 99%